Public health strategies to enhance the National Maternal and Child Care Program: Experiences from a polyclinic - Mora Albear, Gladys (2024)
The National Maternal and Child Care Program (PAMI, by its Spanish acronym) is one of Cuba’s most significant public health initiatives, providing comprehensive care to pregnant women, newborns, and postpartum mothers, leading to internationally recognized health indicators. This study aimed to conduct a historical-logical description of the indicators of the Maternal and Child Care Program at the Policlínico Docente “Carlos Juan Finlay” duringmedical care practices. To achieve this,  ethodological-assistance and managerial strategies were developed, supported by the historical-logical method, to strengthen PAMI—specifcally, the infant mortality rate in children under one year of age at the Policlínico Docente “Carlos Juan Finlay”. The implementation of the scientifc-methodological and managerial strategy was adjusted during medical care practices, improving the outcomes of the Maternal and Child Care Program and its indicators at this polyclinic. These improvements highlight the need to systematize context-specifc transformative actions to strengthen the multidisciplinary team, supported by an interpretative didactic approach that ensures relevance and effectiveness.